Future-Proofing Graduates: A Dynamic Micro-Credential Quality Management System in Higher Education to Ensure Self-Learning Ability, Innovation Capacity, and Career Growth - Surono Surono; Heni Jusuf (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The Micro-Credential Quality Management System (QMS) is designed as a dynamic framework to enhance graduate employability, self-learning ability, and innovation capacity in higher education. This study adopts a research and development (R&D) approach to develop, implement, and validate a QMS that ensures micro-credentials align with industry standards, competency-based learning, and labor market demands. The preliminary validation phase tested the QMS in both vocational and academic settings, involving key stakeholders such as educators, students, and industry professionals. The findings confirm that the system effectively bridges the gap between education and industry, ensuring credible, standardized, and globally recognized micro-credentials. The QMS fosters a flexible and competency-driven learning environment, enabling graduates to acquire targeted skills that enhance career growth and workforce readiness. This study highlights the importance of continuous evaluation, industry collaboration, and standardization in optimizing the implementation of micro-credentials. The research contributes to the advancement of quality assurance in micro-credentialing, reinforcing its role as a transformative tool for lifelong learning and professional development.